Analyzing the Meaning and Legal Implications of Prohibitive Injunctions (Lafadz Nahi) In Islamic Law - Achmad, Zulkifli; Muh. Bambang Taufik; Fatmawati; Abdul Syatar (Al-Zayn: Jurnal Ilmu Sosial, Hukum & Politik, 2026)
The existence of lafadz nahi (prohibitive injunctions) constitutes a central pillar in the epistemology of Ushul Fiqh that dictates the behavioral boundaries of legal subjects. However, the literal application of classical texts lafadz nahi inherently results in legal invalidation (fasad/bathilomplexities of modern state institutions, global legal pluralism, and commercial economic disruptions. This study aims to analyze the semantic construction, interpretative problematics, and legal implications of lafadz nahi concerning the validity of legal acts and contemporary judicial decisions. This research employs a qualitative normative legal study design, applying conceptual, statutory, and comparative approaches. Data were collected through comprehensive library research encompassing primary sources (Qur'anic nash and Hadith) and multidisciplinary secondary literature from reputable international journals, subsequently analyzed using qualitative content analysis and critical hermeneutics grounded in Maqashid al-Syariah. The results indicate that the semantic certainty of a prohibition (qat'i dalalah) serves as the primary foundation for averting interpretative anarchy within the judiciary. Nevertheless, state authorities frequently politicize the interpretation of prohibitions to consolidate hegemonic power, culminating in legal inflation and jurisdictional clashes with global human rights norms (jus cogens). The application of Maqashid al-Syariah proves crucial in resolving these conflicts, as evidenced by the successful harmonization of the prohibition of riba (usury) within Islamic insurance (Takaful) regulations and the deployment of the nahi doctrine to combat labor exploitation. It is concluded that the violation of an absolute lafadz nahi inherently results in legal invalidation (fasad/bathil), and the rational contextualization of prohibitive texts is absolutely imperative to ensure that Islamic law remains relevant as an instrument of justice in the modern era.